Corrosion Rate Analysis and Prediction of the Remaining Life of the Research Vessel to Improve Ship Safety Aspects - Nugroho, Andi Cahyo Prasetyo Tri; Sasmito, Cahyo; Fuadi, Abid Paripurna; Hendrik, Dany; Rahadi, Cakra Wijaya Kusuma; Permana, Rizqi Dian; Fuadi, Noor Muhammad Ridha (Universitas Sebelas Maret, 2023)
Corrosion is a major concern in the marine industry, compromising the safety and integrity of ships. This paper presents a corrosion rate analysis and prediction of the remaining life of the Baruna Jaya IV research vessel using Non-Destructive Testing (NDT) ultrasonic testing to improve ship safety aspects. The NDT ultrasonic testing was conducted on the ship's hull to evaluate the thickness and detect any hidden corrosion. The results were used to develop a corrosion rate model and predict the remaining life of the ship using a probabilistic model. The study found that the corrosion rate of the ship was high, and the remaining life of the ship was estimated to be less than five years. The study’s findings can be used to develop a maintenance and repair strategy to reduce corrosion and improve the safety of the Baruna Jaya IV research vessel.